Microalgae production using photo-bioreactor with intermittent aeration for municipal wastewater substrate and nutrient removal - Afifah, Anshah Silmi; Suryawan, I Wayan Koko; Sarwono, Ariyanti (Komunitas Ilmuwan dan Profesional Muslim Indonesia, 2020)
Microalgae has emerged as a promising approach for removing substrate and nutrient from wastewater with the concomitant biofuel production. The substrate and nutrient removal are influenced by several factors such as C/N ratio, F/M ratio, pH, and DO. This study aims to determine the efficiency of substrate and nutrient removal with the growth rates of microalgae and biomass by varying the addition of aeration and substrate. Intermittently aerated reactors were used with the flow rate of 14 L/minute. The batch reactors were prepared by adding glucose substrate of 50 mg/L (Ra0A), 100 mg/L (Ra0B), and 150 mg/L (Ra0C) without aeration; 50 mg/L (Ra12A), 100 mg/L (Ra12B), and 150 mg/L (Ra12C) with 12-hour aeration, and 50 mg/L (Ra24A), 100 mg/L (Ra24B), and 150 mg/L (Ra24C) with 24-hour aeration. The substrate removal, expressed as chemical oxygen demand (COD) in the reactor with aeration, showed the efficiency of 73.88% ± 2.05 (12-hour aeration), 75.2% ± 3.97 (24hours aeration), and 69.86% ± 5.69(without aeration). Nutrient removal as ammonia-N (NH3-N) gave high removal value of 98.3% ± 0.11 and the removal of nutrient as phosphate (PO3-4) showed the efficiency of 54.3% ± 0.1. The growth rate of microalgae and biomass exhibited the highest value in Ra24C reactor with the values of 0.0229/day and 0.1295/day, respectively. The pH values indicated a shift from normal to alkaline while DO values increased by the addition of 12 and 24-hour aeration.